(untitled) (Journal of Medical & Health Sciences Review, 2025)
Lactobacillus is a genus of Gram-positive, non-spore-forming lactic acid bacteria with significant probiotic potential. These bacteria contribute to human health by producing bioactive compounds such as bacteriocins and hydrogen peroxide, which enhance digestion, support gut microbiota, and reduce the risk of gastrointestinal and other diseases. Yogurt is a rich source of probiotic bacteria, particularly Lactobacillus bulgaricus and Streptococcus thermophilus, which are widely used as starter cultures in dairy fermentation. This study aimed to isolate and identify probiotic Lactobacillus strains from yogurt samples collected from ten different local shops in the NARC region of Islamabad. The samples were cultured on de Man, Rogosa, and Sharpe (MRS) agar, and the isolates were subjected to morphological and biochemical characterization, including Gram staining, catalase, oxidase, and methyl red tests. The results revealed the consistent presence of Lactobacillus bulgaricus and Streptococcus thermophilus in all yogurt samples, with characteristic Gram-positive morphology and negative results for catalase, oxidase, and indole tests. These findings confirm the probiotic potential of locally available yogurt and support its beneficial role in promoting human gut health. The isolated strains may have future applications in the development of probiotic supplements and functional foods.